A Pilot Study to Evaluate the Safety and Clinical Outcomes of Vaccination with Recombinant CEA-MUC-1-TRICOM (PANVAC) Poxviral-based Vaccines in Patients with Metastatic Carcinoma - Gulley, James L. (2008)
PURPOSE: Poxviral vectors have a proven safety record and can be used to incorporate multiple transgenes. Prior clinical trials with poxviral vaccines have shown that immunologic tolerance to self-antigens can be broken. Carcinoembryonic antigen (CEA) and MUC-1 are overexpressed in a substantial proportion of common solid carcinomas. The primary endpoint of this study was vaccine safety, with immunologic and clinical responses as secondary endpoints. EXPERIMENTAL DESIGN: We report here a pilot study of 25 patients treated with a poxviral vaccine regimen consisting of the genes for CEA and MUC-1, along with a triad of costimulatory molecules (TRICOM, composed of B7.1, ICAM-1, and LFA-3) engineered into vaccinia (PANVAC-V) as a prime and fowlpox (PANVAC-F) as booster vaccinations. RESULTS: The vaccine was well-tolerated. Apart from injection-site reaction, no grade II or greater toxicity was seen in more than 2% of the cycles. Immune responses to MUC-1 and/or CEA were seen following vaccine in 9 of 16 patients tested. A patient with clear cell ovarian cancer and symptomatic ascites had a durable (18-month) clinical response radiographically and biochemically, and one breast cancer patient had a confirmed decrease of > 20% in the size of large liver metastasis. CONCLUSIONS: This vaccine strategy appears to be safe, is associated with both CD8 and CD4 immune responses, and has shown evidence of clinical activity. Further trials with this agent, either alone or in combination with immunopotentiating and other therapeutic agents, are warranted.